A Study On Second Language Speaking Anxiety Among UTM Students - Abdullah, Khairi Izwan; Abdul Rahman, Nurul Lina (2010)
A study was carried out to determine the perceptions of University Technology Malaysia students towards the feeling of anxiety they experienced when speaking in the second language. Specifically, the objectives of the study were to investigate students’ anxiety level towards speaking English as a second language and to identify the types of speaking activities that caused high anxiety level among the students. Communication apprehension, fear of negative evaluation and general feeling of anxiety were among the factors studied in the research. The instrument used for the study was adapted from Horwitz’s (1983) Foreign Language Classroom Anxiety Scale (FLCAS). The questionnaire consists of 32 items, each one on a 5-point Likert scale ranging from “strongly agree” to “strongly disagree”. The data obtained were analyzed using SPSS version 10.0 Windows and were represented in the form of descriptive statistics which include percentages and mean. Results from the study show that students experienced moderate level of anxiety.